Using the Conservation Planning Tool to Effectively Recover Northern Bobwhites: An Example for States to Effectively Step-Down the NBCI Plan - Theron M. Terhune; William E. Palmer; Thomas V. Dailey; Billy Dukes; Charles L. McKelvy; John J. Morgan; James C. Pitman; Marc Puckett; Reggie E. Thackston (National Quail Symposium Proceedings, 2017)
The National Bobwhite Conservation Initiative (NBCI) 2.0 provides a sound foundation for recovering northern bobwhites (Colinus virginianus) range-wide, regionally and, to some extent, even locally. However, the NBCI does not provide detailed guidance to states on how to step-down the plan for efficacious delivery of on-the-ground management actions prescribed via biologists within the plan itself. States often must incorporate multiple planning efforts (e.g., state wildlife action plans) and geospatial layers not directly included in the NBCI plan (see NBCI Appendix in these Proceedings) to make tenable decisions which best guide allocation of resources and benefit multiple species of greatest conservation concern. The Conservation Planning Tool (CPT), developed as part of NBCI 2.0, provides the infrastructure for states and conservation organizations to capture biologist information coalesced in the plan while incorporating other data (e.g., species emphasis areas, current CRP implementation, etc.) germane to conservation planning. We use 3 states (Kansas, Florida, and Virginia) to demonstrate the utility of the CPT and to develop a step-down implementation plan, via creation of a habitat prioritization model, for recovery of bobwhites in each state. We explore the implications associated with creation of focal areas with respect to high versus medium ranked areas and underscore the importance of inclusion of major land-use opportunities and constraints prescribed within the plan to garner successful bobwhite recovery. We propose a framework for the integration of monitoring efforts into the step-down model to assess bird response and evaluate NBCI success through estimating bobwhite population density.
Keywords: Colinus virginianus; Conservation Reserve Program; National Bobwhite Conservation Initiative; northern bobwhites